TOXICITY TEST OF KELAKAI LEAF EXTRACT (Stenochlaena palustris) TOWARD WISTAR RATS LIVER (Rattus norvegicus) - Putra Ramadhani, Krisna Erlangga; Krishnawan Firdaus, I Wayan Arya; Wasiaturrahmah, Yusrinie; Aspriyanto, Didit; Wydiamala, Erida (Dentino: Jurnal Kedokteran Gigi, 2025)
Background: Kelakai leaf extract can be used as an alternative wound healing medicine because it contains flavonoid and phenolic compounds that act as antioxidants. Before use, herbal plants must ensure the level of safety that can be obtained from toxicity tests, one of which is in vivo which can be seen from their effect on the liver of Wistar rats based on SGOT and SGPT levels. Purpose: Proving there is no toxic effect from the administration of kelakai leaf extract doses of 2,000, 2,500, and 3,000 mg/kgBW on the liver of Wistar rats based on SGOT and SGPT levels. Method: Pure laboratory experimental research with posttest-only design with control group design, consisting of 16 wistar rats divided into 4 groups with 1 negative control group given distilled water and 3 treatment groups given doses of kelakai leaf extract 2,000, 2,500 and 3,000 mg/kgBW twice a day every morning and evening for 28 days. Results: SGOT and SGPT levels after 28 days were still in the normal range. SGOT levels in treatment groups 1, 2, and 3 were 61.244 U/L, 58.953 U/L, and 53.536 U/L. SGPT levels in treatment groups 1, 2 and 3 were 25.137 U/L, 23.331 U/L, and 21.179 U/L. Based on statistical tests, there were significant differences in all treatment groups. Conclusion: There is no toxic effect from the administration of kelakai leaf extract doses of 2,000, 2,500, 3,000 mg/kgBW orally for 28 days on the liver of Wistar rats based on SGOT and SGPT levels.